EVALUATION OF THE OUTCOME OF ISOPURE 123 FOCAL EXTENSION CATARACTS AT 19-8 HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the results of cataract surgery with implantation of an ISOPURE 123 focal lengthening intraocular lens.Subjects and methods: This study was designed as a prospective descriptive study on 30 eyes of 30 cataract patients who underwent ISOPURE 123 lens implantation surgery at 19-8 Hospital from September 2024 to April 2025.Results: The study included 30 eyes from 30 patients with an average age of 73.5 ± 7.2 (55-87 years old), with a mean distance visual acuity of 1.12 ± 0.54 logMar and corneal astigmatism < 1.0 diopter. Compared to pre-surgery, post-surgery visual acuity increased significantly at all examination times. One month post-surgery, the mean uncorrected distance visual acuity was 0.19 ± 0.11 logMar, the mean uncorrected intermediate visual acuity was 0.12 ± 0.12 logMar, and the mean uncorrected near visual acuity was 0.09 ± 0.07 logMar. Assessment of visual function in patients 3 months after surgery showed that: 73.3% of patients were very satisfied and 26.7% were satisfied with the visual acuity and quality of their eyes after surgery. All surgically treated eyes showed good improvement in visual acuity across all three ranges: distance, intermediate, and near. 3 months after surgery, undesirable symptoms such as halos and glare were only mild in 20% of patients, while 80% were asymptomatic. With the VF-14 scale, 93.3% of patients achieved a score of 75 or higher. The majority of patients had good to very good visual function, allowing them to perform all daily activities normally, the remaining 6.7% of patients experienced minor difficulties in performing daily activities; no patients had severely impaired visual function affecting their daily lives.Conclusion: Cataract surgery with ISOPURE 123 focal lengthening implantation resulted in good visual acuity at distance and intermediate distances. Adverse symptoms such as halos and glare that interfere with daily life were rare.
Keywords: ISOPURE 123 lens, surgical results.